Range‐Wide Genetic Population Structure and Environmental Adaptation in the Eastern Oyster (Crassostrea virginica ) Provides Insight for Aquaculture - Madeline G. Eppley; Kiran Bajaj; Camille Rumberger; Elisabeth Leung; Nicole Mongillo; Jessica Small; Katie E. Lotterhos (Molecular Ecology, 2026)
Selective breeding in aquaculture is necessary to establish food security and meet demand for sustainably produced protein. An informed selective breeding program requires understanding how population structure, environmental adaptation, and human activities shape natural genetic variation in wild conspecifics. Unfortunately, wild variation remains poorly characterised for many commercially important aquaculture species. Here, we conduct the first range‐wide study of genomic population structure for the eastern oyster ( Crassostrea virginica ) across thousands of miles (Texas, USA to Eastern Canada) using a 200K SNP array. We integrate population structure analyses, genotype‐environmental associations, and structural variant detection to identify adaptive loci and quantify human‐mediated genetic impacts. Our data confirm two ancestral clusters with a phylogeographic break between the Gulf and Atlantic (F ST = 0.16) and highlight patterns of substructure within each region. We find evidence of unexpected patterns of genomic variation in two locations: evidence of Gulf ancestry in a mid‐Atlantic estuary (Chesapeake Bay), and evidence of Atlantic ancestry in a Gulf estuary (Apalachicola Bay). While we cannot definitively determine the causes of these unexpected patterns, we show that they are consistent with direct and indirect human impacts in these estuaries. Genotype‐environment association analyses with in situ temperature and salinity measurements were used to identify putatively adaptive loci, including SNPs within large structural variants (> 1 Mb). Our results identified genomic targets for aquaculture breeding programs aimed at climate resilience, reveal complex patterns of human impacts in managed systems, and demonstrate how seascape genomics can be used to improve aquaculture outcomes.

Genomic Offsets Predict Survival With Low Accuracy in a Marine Common Garden - Camille A. Rumberger; Madeline G. Eppley; Kiran Bajaj; Nicole Mongillo; Shelley Katsuki; Jessica A. Small; Katie E. Lotterhos (Molecular Ecology, 2026)
Predicting how populations will respond to climate change is an urgent priority in evolutionary and conservation biology. Genetic and environmental influences have long been known to impact responses to shifting climates, giving rise to the development of genomic offset methods that attempt to predict the degree of maladaptation following environmental change. Although these methods have the potential to improve our understanding of populations' responses to climate change, questions remain about how well they predict fitness in a diversity of systems. Here, we pair genomic offsets with a large‐scale common garden experiment to investigate how fitness of a marine mollusc, Crassostrea virginica , varies across environmental gradients and to validate offset predictions against empirical fitness. We find that at two common garden sites in the Chesapeake Bay, Northern oysters had the lowest survival and growth, whereas Southern oysters had similar survival and growth to local wild oysters and selection lines. We compared survival and length to offset predictions, finding higher method performance at the lower salinity, moderate disease site than at the higher salinity, higher disease site. The inclusion of disease in the offset model training additionally impacted offset method performance, though the effect varied between common garden sites, fitness proxies and across methods. Despite a nearly 50% difference in survival across sites, the magnitude of offset predictions to both common gardens was similar, highlighting issues with extrapolating offset predictions across species ranges. Performance of genomic offset methods in this system was not adequate to make real‐world predictions to environmental stressors.

Genomic selection for low salinity tolerance in the eastern oyster Crassostrea virginica in Louisiana and Chesapeake Bay populations - Lindsey C. Schwartz; Beth A. Stauffer; Romain Lavaud; Megan K. La Peyre; Ann Fairly Pandelides; Alexandra J. McCarty; Jessica M. Small; Louis V. Plough (Aquaculture, 2026)

Genetic parameters for dermo challenge survival in a Virginia, U.S. eastern oyster breeding population - Dina A. Proestou; Thomas A. Delomas; Jessica Moss Small (Aquaculture, 2025)

Broodstock genetics, more than ploidy alone, explains oyster resilience at farm sites impacted by sudden unusual mortality syndrome - Tal Ben-Horin; Corinne Audemard; Mark Ciesielski; Tom Clerkin; Nicole Krogman; Jonathan Lucas; Rachel T. Noble; Jessica Moss Small; Kimbery Reece; Ami Wilbur (Aquaculture, 2025)

Corrigendum to “Survival and toxin accumulation in Crassostrea virginica larvae following exposure to various Dinophysis species” [Aquaculture, Volume 602, 30 May 2025, 742294] - Nour Ayache; Marta Sanderson; Jessica Small; Amanda B. Chesler-Poole; Sabrina D. Giddings; Lisa Campbell; Vera L. Trainer; Michael L. Brosnahan; Juliette L. Smith (Aquaculture, 2025)

Survival and toxin accumulation in Crassostrea virginica larvae following exposure to various Dinophysis species - Nour Ayache; Marta Sanderson; Jessica Small; Amanda B. Chesler-Poole; Sabrina D. Giddings; Lisa Campbell; Vera L. Trainer; Michael L. Brosnahan; Juliette L. Smith (Aquaculture, 2025)

Morpholino oligomer delivery via bath immersion for use in reverse genetic studies on the early development of eastern oysters (Crassostrea virginica) - Lan Xu; Jessica Moss Small; Shannon M. Hood; Mingli Zhao; Louis V. Plough; Ten-Tsao Wong (Aquaculture, 2025)

Probiotic treatment modulates the bacterial microbiome of larval eastern oysters, Crassostrea virginica, in hatcheries - Evelyn Takyi; Rebecca J. Stevick; Erin M. Witkop; Lauren Gregg; Amanda Chesler-Poole; Jessica Moss Small; Meredith M. White; Robbie Hudson; Cem Giray; David C. Rowley; David R. Nelson; Marta Gomez-Chiarri (Aquaculture, 2024)

Development and Evaluation of High-Density SNP Arrays for the Eastern Oyster Crassostrea virginica - Ximing Guo; Jonathan B. Puritz; Zhenwei Wang; Dina Proestou; Standish Allen; Jessica Small; Klara Verbyla; Honggang Zhao; Jaime Haggard; Noah Chriss; Dan Zeng; Kathryn Lundgren; et al. (Marine Biotechnology, 2023)

Detection of toxins and harmful algal bloom cells in shellfish hatcheries and efforts toward removal - Marta P. Sanderson; Karen L. Hudson; Lauren S. Gregg; Amanda B. Chesler-Poole; Jessica M. Small; Kimberly S. Reece; Ryan B. Carnegie; Juliette L. Smith (Aquaculture, 2023)